A predictive model of serum 25-hydroxyvitamin D in UK white as well as black and Asian minority ethnic population groups for application in food fortification strategy development towards vitamin D deficiency prevention. Issue 173 (October 2017) - O'Neill, Colette M.; Kazantzidis, Andreas; Kiely, Mairead; Cox, Lorna; Meadows, Sarah; Goldberg, Gail; Prentice, Ann; Kift, Richard; Webb, Ann R.; Cashman, Kevin D.
Highlights: The first UVB-serum 25(OH)D model for white and dark-skinned population groups. Predicted v. measured% serum 25(OH)D <30 nmol/L was 23.2% v. 23.1%, respectively. % serum 25(OH)D <30 nmol/L shown to decrease with addition of vitamin D to diet. Such mathematical models can help design vitamin D food fortification strategies. Abstract: Within Europe, dark-skinned ethnic groups have been shown to be at much increased risk of vitamin D deficiency compared to their white counterparts. Increasing the dietary supply of vitamin D is potentially the only modifiable environmental component that can be used to prevent vitamin D deficiency among dark-skinned ethnic groups living at high latitude. Empirical data to support development of such strategies is largely lacking. This paper presents the development and validation of an integrated model that may be adapted within the UK population to design fortification strategies for vitamin D, for application in both white and black and Asian minority ethnic (BAME) population groups. Using a step-wise approach, models based on available ultraviolet B (UVB) data, hours of sunlight and two key components (the dose-response of serum 25-hydroxyvitamin D [25(OH)D] to UVB in white and BAME persons and the dose-response of 25(OH)D to vitamin D) were used to predict changes population serum 25(OH)D concentrations throughout the year, stratified by ethnicity, 'via increases' in dietary intake arising from food fortification simulations. The integrated model successfully predicted measured average wintertime 25(OH)D concentrations in addition to the prevalence of serum 25(OH)D <30 nmol/L in adult white and BAME individuals (18–70 y) in the UK-based National Diet and Nutrition Survey both separately (21.7% and 49.3% predicted versus 20.2% and 50.5% measured, for white and BAME, respectively) and when combined at UK population-relevant proportions of 97% white and 7% BAME (23.2% predicted versus 23.1% measured). Thus this integrated model presents a viable approach to estimating changes in the population concentrations of 25(OH)D that may arise from various dietary fortification approaches.